Optimization of PBB Data Updates Through Collaboration of UNTIDAR Students with BPPKAD in Three Districts of Magelang Regency - Rendi Ramadani Saputra; Silvia Veni; Nurul Janah; Siti Nurlaela; Vira Marinda; Endah Dwi; Yuliana Indah; Adnan Syarif; Candra Dewi; Erika Maulan (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
The Community Service Program (KKN) represents a collaborative effort between students of Universitas Tidar (UNTIDAR) and the Regional Revenue, Financial Management, and Asset Agency (BPPKAD) of Magelang Regency aimed at enhancing the updating of Land and Builidng Tax (PBB) data. This activity was carried out in three sub district, namely Mungkid sub district, Mertoyudan sub district, and Muntilan sub district, by utilizing the SiPBB Trengginas website. In a direct practice approach, students play an active role in assisting village officials in the process of data mutation, tax object updates, data correction, and cancellation of inappropriate SPPT. The result of this activity show that the collaboration has succeeded in improving the accuracy of PBB data, efficiency in regional tax administration, and public understanding of the importance of data updating. This program not only provides direct benefits to the community and local government, but also provides practical experience for students in applying knowledge to solve problem in the field.